Avaliação da viabilidade de implementação de política de hedge de preços em empresas de mineração utilizando simulação de Monte Carlo - Werneck, Fernando Vieira (2018)
The volatility of the market price of their products is one of the biggest sources of variability for the mining sector. Therefore, reducing or elimination this factor, significantly changes their risk profile. This dissertation discusses the potential benefit for mining companies of adopting a price hedge policy. Having a price hedge will be positive when prices go down and especially important when they reach stress levels. Consequently, a traditional deterministic approach, where the model inputs are fixed, would not support an appropriate analysis. As an alternative, with Monte Carlo simulation, it is possible to evaluate a wider range of possible outcomes and asses tail risk into the analysis. Therefore, this method was chosen to compare the economic results of a company under two different scenarios: when they allow their prices to fluctuate according to the market and under a fixed prices policy. A greenfield copper mine project was chosen to represent the operational and financial complexity of the sector. The interaction between financial leverage, company default risk, cost of debt and cash flow volatility is a key factor to determine whether it would be profitable to adopt a price hedge policy. The results show that, under certain circumstances, it is possible to create economical value by fixing their prices. Those factors are: lower direct costs, lower volatility of production and costs, higher commodities prices.